2021
DOI: 10.1002/cnr2.1566
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CD148 Q276P/R326Q polymorphisms in A431D epidermoid cancer cell proliferation and epidermal growth factor receptor signaling

Abstract: Background CD148 is a transmembrane protein tyrosine phosphatase that is expressed in multiple cell types. Previous studies have shown that CD148 dephosphorylates growth factor receptors and their signaling molecules, including EGFR and ERK1/2, and negatively regulates cancer cell growth. Furthermore, research of clinical patients has shown that highly linked CD148 gene polymorphisms, Gln276Pro (Q276P) and Arg326Gln (R326Q), are associated with an increased risk of several types of cancer. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It has a homotrimeric structure of 450 kDa and Takahashi et al reported that it binds to the extracellular domain of CD148 with high affinity and specificity and increases CD148 phosphatase activity. Follow-on studies have shown that naturally occurring variations in the CD148 extracellular domain Q276P/R326Q mutations do not have major effects on TSP1-CD148 interaction, indicating that these residues are not involved [36,37]. In contrast with the soluble secreted TSP1, syndecans are cell-surface heparan sulfate proteoglycans that regulate many cellular functions.…”
Section: Ligands For R3 Ptps and Interactions Mediated Via The Extrac...mentioning
confidence: 99%
“…It has a homotrimeric structure of 450 kDa and Takahashi et al reported that it binds to the extracellular domain of CD148 with high affinity and specificity and increases CD148 phosphatase activity. Follow-on studies have shown that naturally occurring variations in the CD148 extracellular domain Q276P/R326Q mutations do not have major effects on TSP1-CD148 interaction, indicating that these residues are not involved [36,37]. In contrast with the soluble secreted TSP1, syndecans are cell-surface heparan sulfate proteoglycans that regulate many cellular functions.…”
Section: Ligands For R3 Ptps and Interactions Mediated Via The Extrac...mentioning
confidence: 99%
“…It has a homotrimeric structure of 450 kDa and Takahashi et al reported that it binds to the extracellular domain of CD148 with high affinity and specificity and increases CD148 phosphatase activity. Follow-on studies have shown that naturally ocurring variations in the CD148 extracellular domain Q276P/R326Q mutations do not have major effects on TSP1-CD148 interaction indicating that these residues are not involved [36,37]. In contrast with the soluble secreted TSP1, syndecans are cell surface heparan sulfate proteoglycans that regulate many cellular functions.…”
Section: Ligands For R3 Ptps and Interactions Mediated Via The Extrac...mentioning
confidence: 99%